Teori kritis terhadap analisis sitasi untuk kajian kuantitatif sains dan evaluasi kinerja riset - Yaniasih Yaniasih (Perpustakaan Universitas Gadjah Mada, 2020)
Introduction. Citation is the main indicator in research performance evaluation using the quantitative approach. There have been many criticisms of citations since they were used half a century ago, but they have not yet succeeded in bringing new concepts and methods. This paper aims to criticize and propose a new approach to citation analysis. Data Collection Method. A contemporary critical theory methodology was adopted as a framework to collect and analyze the data. Scientific publications related to citation analysis was collected from several databases such as Google scholar, Microsoft academic search, dan Garuda Ristekdikti. Analysis Data. Publications data were critically reviewed and analyzed narratively by using open coding. Results and Discussions. The results mapped the lack of citation analysis form various aspects: (1) criticism of the positivist paradigm which did not succeed in achieving its objectives, (2) criticism of methods that produce invalid results, and (3) criticism of ethical issues of the researcher and bias in implementation. The proposed solution and recommendation is to change the citation analysis method from a simple measurement of bibliographic data to text and context analysis based on a computer science approach (machine learning techniques). Conclusion. This new method has the potential to be developed within the framework of quantitative in Science and Technology studies to overcome existing criticisms. Subsequent multidisciplinary studies are needed to lay a strong philosophical and technical foundation particularly in applying the in-text citation analysis method for evaluating research performance in accordance with the Indonesian context.